Marketing Strategy Analysis to Boost Tourism Visits in NTT - Sihombing, Midian Immanuel; Sinurat, Donal Anry Jaya (Entrepreneurship Faculty, Universitas Garut, 2025)
Tourism is a strategic sector that significantly contributes to economic growth, including in East Nusa Tenggara (NTT) Province, which possesses rich natural and cultural attractions. However, fluctuations in tourist visits indicate the need to evaluate the effectiveness of current marketing strategies. This study aims to analyze tourism marketing strategies in NTT using a SWOT analysis approach and the marketing mix (7Ps), which includes product, price, place, promotion, people, process, and physical evidence. The research method employed is descriptive qualitative, using secondary data from BPS and the Ministry of Tourism and Creative Economy. The SWOT analysis results in SO, WO, ST, and WT strategies that focus on digital promotion, human resource development, sustainable tourism, and integrated planning. This study provides practical strategy recommendations to increase tourist visits and support the inclusive and sustainable growth of the tourism sector in NTT.